Optimization of Population Administration Services with the Use of Klampid New Generation in Pacarkembang Village - Rini Kusumawati; Dida Rahmadanik; Yusuf Hariyoko (PT FORMOSA CENDEKIA GLOBAL, 2022)
Public service is one of the essential things in human life. Until now, public services in Indonesia still have many deficiencies, and this situation has also caused Indonesian public services to receive a lot of criticism from the public. Therefore, the Surabaya City Government decided to reform the population and registration system called the New Generation Klampid (KNG). The purpose of this research is to describe the New Generation of Klampid (KNG) in optimizing the quality of service in Surabaya and taking place in the Boyfriend Village. This research uses qualitative method and descriptive type. The selected informants in this study consisted of structural officials and residents. Data collection was carried out through in-depth interviews, observation and documentation. The results of this study indicate that the New Generation Klampid (KNG) program to improve service optimization in Surabaya is running quite well. This is demonstrated by the existence of innovations that bring more benefits to people who wish to register for population administration and civil registration. Even though the lack of socialization still causes some people not to know about technology